Enhancing Financial Literacy through Waste Bank Education as a Sustainable Economic and Environmental Solution : English - Sri Maitri, Wayan; Putra P, Komang Widhya Sedana; Ni Wayan Lasmi (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
This community service program was conducted at a small and medium-sized enterprise (SME) in Padangsambian Klod, Denpasar, with the aim of enhancing financial literacy through waste bank education as a sustainable economic and environmental solution. The activity, carried out in January 2025, was designed as a one-day intervention involving preparation, introduction, practical workshop, financial literacy training, and reflection. The program adopted a participatory approach, ensuring active involvement of SME owners and local community members. Results showed a significant improvement in participants’ awareness and attitudes toward waste management and financial practices. Before the program, most participants perceived waste as valueless and had limited understanding of basic financial management. Afterward, they demonstrated better knowledge of waste as an asset, applied simple bookkeeping techniques, and expressed stronger motivation to save and engage actively in community initiatives. The integration of waste bank education with financial literacy proved effective in linking environmental responsibility with economic empowerment. Furthermore, the cultural relevance of the program increased participants’ acceptance and ownership, fostering opportunities for replication in other communities. In conclusion, this initiative demonstrates that short, well-structured interventions can generate meaningful changes and contribute to sustainable community development.